Formação continuada, desafios e superações para professores de educação física nos anos iniciais do município de Santa Maria – RS - Souza, Miria Jair Vieira de (2018)
The research was based on the research on the possibilities of continuing education of Physical Education teachers who work in the initial years, in the municipality of Santa Maria, RS. The methodology was characterized as dialectical critic appropriating historical materialism as theoretical foundation. As research techniques, we used document analyzes that govern the right to continuous training at the municipal level; application of questionnaires with teachers of Physical Education of this same network of education and another questionnaire carried out with the pedagogical sector of the Municipal Secretariat of Education Santa Maria. The work is in line with the research line "Sociocultural and Pedagogical Aspects of Physical Education" with emphasis in the content category - Continuing Education, as well as in the methodological category of the totality in the initial years of the teaching area in question. The qualification of teachers through continuous training, from the beginning shows that the process of appropriation of knowledge and pedagogical actions are constantly built, presenting itself fundamental and its absence opens a huge gap in the professional life of teachers, making the inherent transformations impossible. school and social context. Therefore, we confirm our hypothesis raised initially in this study; that the continued formation in the municipal network is precarious and does not sufficiently consider the contributions that the pedagogical and didactic work needs.